The Impacts of Oil Price Fluctuations on Revealed Comparative Advantage of Manufacturing Commodities for ASEAN-5 Economies - Azman Aziz, Mukhriz Izraf; Dahalan, Jauhari (International Journal of Energy Economics and Policy, 2015)
This paper attempts to quantify the effects of oil price fluctuations on revealed symmetric comparative advantage (RSCA) for 95 manufacturing commodities of 5 ASEAN countries from 1991 to 2012. Using Zellner’s (1962) seemingly unrelated regression (SURE) model, oil price fluctuations negatively affect RSCA of more than 60% of the manufacturing commodities estimated. This is true especially for low-technology (LT1 & LT2) and medium-technology (MT3) commodities. The paper also found that endowment variables such as labour and capital stock significantly affects RSCA for more than 50% of the equations, giving support to Ricardian and Heckscher-Ohlin theorem of comparative advantage. Keywords: Revealed Comparative Advantage; Oil Price Shocks; International Trade JEL Classifications: C33; F11; N50